2020
DOI: 10.1038/s41598-020-57693-5
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality navigation with intraoperative 3D imaging vs fluoroscopy-assisted free-hand surgery for spine fixation surgery: a matched-control study comparing accuracy

Abstract: This study aimed to compare screw placement accuracy and clinical aspects between Augmented Reality Surgical Navigation (ARSN) and free-hand (FH) technique. Twenty patients underwent spine surgery with screw placement using ARSN and were matched retrospectively to a cohort of 20 FH technique cases for comparison. All ARSN and FH cases were performed by the same surgeon. Matching was based on clinical diagnosis and similar proportions of screws placed in the thoracic and lumbosacral vertebrae in both groups. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 31 publications
0
72
0
Order By: Relevance
“…This in turn resulted in a favorable simulated Gertzbein grading (100% accuracy), well in line with the vast majority of recent studies that typically report 98 -100% accuracy 34,[37][38][39][40][41] . Notably, the results of this study indicate a superior clinical, as well as technical accuracy, for the ARSN system with robotic guidance compared to previous results when the same ARSN system is used without robotic assistance (Table 2) [15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This in turn resulted in a favorable simulated Gertzbein grading (100% accuracy), well in line with the vast majority of recent studies that typically report 98 -100% accuracy 34,[37][38][39][40][41] . Notably, the results of this study indicate a superior clinical, as well as technical accuracy, for the ARSN system with robotic guidance compared to previous results when the same ARSN system is used without robotic assistance (Table 2) [15][16][17][18][19] .…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies have reported the development of a surgical navigation system based on augmented and virtual reality navigation in a hybrid operating room (OR) setup [15][16][17][18][19] . A clinical accuracy of 89% without, and 100% with instrument tracking, in MIS surgery has previously been demonstrated with the augmented reality surgical navigation system (ARSN) 17,18 .…”
mentioning
confidence: 99%
“…For this purpose, both endocast and virtual dissection images are used. Virtual reality supports the interactive sharing of the three-dimensional images during the simulated operation and also can guide the invasive procedures and operations, especially in such fields of orthopedics and neurosurgery [ 47 , 48 ]. As the heart is a highly moving structure, the application of virtual reality into the clinical cardiovascular fields can be challenging.…”
Section: Advanced Application Of the Three-dimensional Imagingmentioning
confidence: 99%
“…Currently, many scientific papers on the use of augmented reality in various fields of medicine have been published: neurosurgery, cardiology, urology, plastic surgery, including dentistry and maxillofacial surgery (Ayoub & Pulijala, 2019;Elmi-Terander et al, 2020;Kim, Kim, & Kim, 2017;Kwon, Park, & Han, 2018). However, most of them are descriptions https://doi.org/10.17993/3ctecno.2020.specialissue6.21-31 of individual clinical cases or their series, which certainly does not have a very high class of evidence (Bosc et al, 2019).…”
Section: Introductionmentioning
confidence: 99%